CONSTRUCTION AND MANAGEMENT OF MULTIVARIATE INDICES FOR CHARACTERIZING THE QUALITY OF THE MARINE COASTAL PERÚ - Adriazola Cruz, Rosa Ysabel (2010)
The main objective of this study is to build indicators based on multivariate statistical methods considering the variables temperature, oxygen, pH, total suspended solids which to characterize the quality of the marine environment in particular the Bay of Ferrol. Due to the complexity of the quality characteristics related to marine environment, we used multivariate                statistical methods in order to recognize a pattern or explanatory structure, and also hypotheses for further study. Based on Factor Analysis has built a quality rating of the marine environment in particular are the results obtained in the Bay of Ferrol.